QARAQALPAQ HÁM INGLIS TILLERINDEGI ATLÍQTÍŃ SEPLIK KATEGORIYASÍNÍŃ SALÍSTÍRMALÍ ANALIZI - Bekbergenov, H.U. (SCIENCE and SOCIETY, 2024)
The article provides a comparative analysis of the case systems of nouns in the English and Karakalpak languages. During the research, we found out that there are similarities in the morphological structure of the nominative and genitive cases in the Karakalpak and English languages. And the meanings of other cases of nouns in the Karakalpak language are mainly expressed through prepositions and word order in the English language.